1995
DOI: 10.1037/0735-7028.26.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Personality feedback consultation to families in a managed mental health care practice.

Abstract: This article presents personality assessment as valuable in expediting favorable outcomes in mental health service delivery. The unique role of the examining psychologist is discussed with respect to assessment paradigms, behavior sampling, and eliciting patient "ownership" of solutions. Solutionoriented therapy is presented as promoting client adaptiveness from a customer-oriented point of view. A consultation-feedback model is described, which integrated these themes. Several case examples are offered to ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Finn (1996Finn ( , 2003 and Finn and Kamphuis (2006, in press) have provided detailed adult case illustrations containing verbatim transcripts from the clinical sessions. DuBose (2002); Fischer (1985Fischer ( /1994Fulmer, Cohen, and Monaco (1985); Handler (2007);Michel (2002); Mutchnick and Handler (2002); Pollack (1988); Purves (2002);and Quirk, Strosahl, Kreilkamp, and Erdberg (1995) have published clinical case studies of collaborative assessment with children or adolescents. In most of these, parents report gaining a better understanding of their children's problems and feeling more effective in their parenting and in pursuing of appropriate services, whereas children have shown decreased behavioral problems and improved mood, social functioning, and school adjustment.…”
Section: Research On Collaborative and Therapeutic Assessmentmentioning
confidence: 98%
“…Finn (1996Finn ( , 2003 and Finn and Kamphuis (2006, in press) have provided detailed adult case illustrations containing verbatim transcripts from the clinical sessions. DuBose (2002); Fischer (1985Fischer ( /1994Fulmer, Cohen, and Monaco (1985); Handler (2007);Michel (2002); Mutchnick and Handler (2002); Pollack (1988); Purves (2002);and Quirk, Strosahl, Kreilkamp, and Erdberg (1995) have published clinical case studies of collaborative assessment with children or adolescents. In most of these, parents report gaining a better understanding of their children's problems and feeling more effective in their parenting and in pursuing of appropriate services, whereas children have shown decreased behavioral problems and improved mood, social functioning, and school adjustment.…”
Section: Research On Collaborative and Therapeutic Assessmentmentioning
confidence: 98%
“…He concluded that with a focal assessment it "often is possible to accomplish in 11,5 to 21/2 days what would require weeks or months of once-a-week sessions" (p. 554). Fulmer, Cohen, and Monaco (1985); Quirk, Storsahl, Kreilkamp, and Erdberg (1995); and Pollak (1988) presented case examples where psychological testing was used to help parents and school personnel gain empathy for children with learning and behavioral problems and to develop effective interventions. Moffett et al (1996) described the use of personality testing to assist the formation of a "therapeutic community" among men in inpatient treatment for severe substance dependence.…”
Section: Using Psychological Assessment As a Treatment In Itselfmentioning
confidence: 99%
“…It also diminishes the gap between assessment and treatment, which is an important criterion for demonstrating value to clients/customers. Therapeutic benefits of this feedback are most likely to occur when the feedback comes shortly after the assessment and the clients become active participants in evaluating the accuracy and relevance of the results (Hanson, Claiborn, & Kerr, 1997;Newman & Greenway, 1997;Quirk, Strosahl, Kreilkamp, & Erdberg, 1995).…”
Section: Financial Efficacymentioning
confidence: 99%